2017
DOI: 10.1371/journal.pone.0175228
|View full text |Cite
|
Sign up to set email alerts
|

Exploring drivers for safe male circumcision: Experiences with health education and understanding of partial HIV protection among newly circumcised men in Wakiso, Uganda

Abstract: IntroductionAbout 2.5 million men have voluntarily been circumcised since Uganda started implementing the WHO recommendation to scale up safe male circumcision to reduce HIV transmission. This study sought to understand what influences men's circumcision decisions, their experiences with health education at health facilities and their knowledge of partial HIV risk reduction in Wakiso district.MethodsData were collected in May and June 2015 at five public health facilities in Wakiso District. Twenty-five in-dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 37 publications
(47 reference statements)
2
11
1
Order By: Relevance
“…A study by L'Engle et al (2014) showed that men had a good understanding of the partial protection offered by VMMC as these participants were able to describe how circumcision reduced HIV transmission and the intention to use other HIV protective measures such as practicing safe sexual intercourse. Similar findings were reported in a later study by Kibira et al (2017). The difference in such findings may be attributed to the levels of education among interviewed participants, the general practice of circumcision, and the cultural context.…”
Section: Discussionsupporting
confidence: 87%
“…A study by L'Engle et al (2014) showed that men had a good understanding of the partial protection offered by VMMC as these participants were able to describe how circumcision reduced HIV transmission and the intention to use other HIV protective measures such as practicing safe sexual intercourse. Similar findings were reported in a later study by Kibira et al (2017). The difference in such findings may be attributed to the levels of education among interviewed participants, the general practice of circumcision, and the cultural context.…”
Section: Discussionsupporting
confidence: 87%
“…The ndings further show that improved knowledge of the importance for personal hygiene and protection from HIV and other STIs were facilitators for VMMC. Other studies have shown comparable levels of knowledge of health bene ts of VMMC between the general population and a key population of boda-boda riders [24,33]. However, we found varied incorrect information regarding VMMC.…”
Section: Discussioncontrasting
confidence: 45%
“…Where inconsistences existed during analysis, consensus was reached in meetings with all the other research team members. Thematic content analysis following prior themes from similar studies was applied [9,10,12,[23][24][25].…”
Section: Data Management and Analysesmentioning
confidence: 99%
“…Although we did not intend to stratify selection of participants by age, younger (below 25 years of age) and older participants were evenly represented. The drivers of the circumcision decisions of these men are discussed in a related paper [ 17 ]. The upper age limit (59 years) is in line with AIDS indicator survey age group while the lower age limit (18 years) is the adult age of consent in Uganda.…”
Section: Methodsmentioning
confidence: 99%